Interspecific Hybrids Between Pelargonium × hortorum and Species From P. Section Ciconium Reveal Biparental Plastid Inheritance and Multi-Locus Cyto-Nuclear Incompatibility - Breman, Floris C.; Snijder, Ronald C.; Korver, Joost W.; Pelzer, Sieme; Sancho-Such, Mireia; Schranz, M. Eric; Bakker, Freek T. (Frontiers in Plant Science, 2020)
The genetics underlying Cyto-Nuclear Incompatibility (CNI) was studied in Pelargonium interspecific hybrids. We created hybrids of twelve closely related crop wild relatives (CWR) with the ornamental P. x hortorum. Ten of the resulting twelve (F1) interspecific hybrids segregate for chlorosis suggesting biparental plastid inheritance. The segregation ratios of the interspecific F2 populations show nuclear interactions of one, two or three nuclear genes regulating plastid function dependent on the parents. We further validated that biparental inheritance of plastids is common in section Ciconium, using diagnostic PCR primers. Our results pave the way for using the diverse species from section Ciconium, each with its own set of characteristics, as novel sources of desired breeding traits for P. x hortorum cultivars.